Fine slicing of the value chain and offshoring of essential activities: empirical evidence from European multinationals - Linares-Navarro, Esmeralda; Pedersen, Torben; Pla-Barber, José (Journal of Business Economics and Management, 2014)
The offshoring of more advanced activities is increasing and a debate about the limits of offshoring has emerged. Companies are fine-slicing their value chains, and moving beyond the offshoring of peripheral and non-core activities to the offshoring of advanced and essential activities that are closer to their core (e.g. research, design and product development). The challenge is to understand the limits of offshoring and the most appropriate modes of offshoring. The purpose of this paper is to analyze what activities are offshorable and how best to govern offshored activities. We argue that companies are redefining their core activities and in this process, some essential activities previously viewed as core activities are being detached from the core, and they become more offshorable. The study uses a sample of 565 offshoring operations conducted by 263 multinational companies from 15 European countries. A logistic regression was used to analyze the relationship between the activities offshored (non-core versus essential activities) and the offshoring mode implemented (captive offshoring versus offshore outsourcing). We find that essential activities are typically offshored using the captive mode, while offshore outsourcing is commonly used to offshore non-core activities; and this trend is even more pronounced in knowledge-intensive companies where interfaces between the various activities are less standardized. This paper offers managers and CEOs an integrative tool that can make easier decisions regarding offshoring modes (captive versus offshore outsourcing) and serves as a reference point for further analyses of the implementation of offshoring strategies in multinational enterprises.